trans-4-[(Phenylsulfonyloxy)methyl]cyclohexanecarboxylic acid - Hu Zheng; Qing-Rong Qi; Yu-Feng Liang (Acta Crystallographica Section E, 2008)
The title compound, C14H18O5S, is an important intermediate for the synthesis of poly(amidoamine) dendrimers. The cyclohexane ring adopts a chair conformation with its two substituents in equatorial positions. In the crystal structure, molecules form centrosymmetric dimers via O—H...O hydrogen bonds.